Broadband Network Fiber to the Home (FttH) Design for Improving Performance of Information and Telecommunication Network in Riau University - Safrianti , Ery; Sari, Linna Oktaviana; Retdha Yuhana, Dwi Putra (International Journal of Electrical, Energy and Power System Engineering, 2018)
Increased demand for information and telecommunications at the University of Riau demanding reliable carrier network availability. Copper cable network that now exists less support for multimedia network performance. Therefore, it is necessary to design a new access networks. One alternative is to implement fiber optic technology Fiber to the Home (FttH). This research design a FttH network for information access needs on the campus site, located in Panam, Pekanbaru. The results show the needs of Optical Network Terminal (ONT) as many as 209 units and 34 units of Optical Distribution Point (ODP), using passive splitter 1: 8 type of wall. Optical Distribution Cabinet (ODC) 1 unit to serve all the region in UR with a capacity of 24 core, using ODC 144 type. Calculation of the sample data taken, showing the speed of each customer in the Engineering Faculty using FttH is approximately 3 Mbps. Link Budget Calculations indicate that power received by each faculty on average -23.17 dB, it can be concluded FttH network design is feasible and appropriate ethical standards that have been determined shall not exceed -28 dB. Attenuation of each faculty obtained the average value of -21.17 dB.